2016
DOI: 10.5815/ijitcs.2016.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Web Service Component Reusability Evaluation: A Fuzzy Multi-Criteria Approach

Abstract: Abstract-The service oriented architecture supports reusable components. Component reusability is one of the important features while designing web services for reuse. The reusability is an ideal and key factor to improve the quality and production rate of software. It becomes very helpful for quality assurance, if such quality parameters can be quantified. Non functional quality parameters like reusability are not easy to measure and quantify. This paper attempts to quantify reusability using fuzzy multi crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The authors [21] have demonstrated the Buy vs Build strategy for selecting components for a modular system using fuzzy bi-criteria optimization model. The researchers [22] have done an assessment of reusability of web service components that can help in component selection too.…”
Section: Related Workmentioning
confidence: 99%
“…The authors [21] have demonstrated the Buy vs Build strategy for selecting components for a modular system using fuzzy bi-criteria optimization model. The researchers [22] have done an assessment of reusability of web service components that can help in component selection too.…”
Section: Related Workmentioning
confidence: 99%